Bartonella spp. and Typhus Group Rickettsiae among Persons Experiencing Homelessness, São Paulo, Brazil - Faccini-Martínez, Álvaro A.; Kmetiuk, Louise Bach; Blanton, Lucas S.; Felipetto, Laís Giuliane; Gravinatti, Mara Lúcia; Timenetsky, Jorge; Gonçalves, Luiz Ricardo [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Figueiredo, Fabiano Borges; dos Santos, Andrea Pires; Labruna, Marcelo B.; et al. (Centers for Disease Control and Prevention (CDC), 2023)
Persons experiencing homelessness in São Paulo, Brazil, were seropositive for Bartonella spp. (79/109, 72.5%) and typhus group rickettsiae (40/109, 36.7%). Bartonella quintana DNA was detected in 17.1% (14/82) body louse pools and 0.9% (1/114) blood samples. Clinicians should consider vectorborne agents as potential causes of febrile syndromes in this population.